The right contextual information determining the success of communication on translation - Zu, Zera (Applied Translation, 2021)
As relevance theory shows, the success of communication crucially depends on the right contextual information being highly accessible at the right time. Thus it is not sufficient that this information is physically available somewhere in the receptor language; to become effective for comprehension it must be highly accessible mentally to the reader or hearer at the time when it is needed. Thus while it is true in a general way that the translation of Old Testament portions is important because they provide background information necessary for understanding the New Testament, for it to be profitable for the comprehension of a particular New Testament passage, readers must be able to access in their minds just those pieces of information from the Old Testament that are relevant to this specific passage.